'Produce More Coal' = 'Produce More Silicosis'? Re-training, Re-employment, and Respiratory Illnesses in the South Wales Coalfield, 1938–1945. Issue 3 (December 2017) - Crowley, Mark J.
Abstract : By 1939, the coal industry, like all industries, was facing the pressure of war, bringing an increased concern not only for the state of the industry, but for the health of its workers. The government's preoccupation with production in preparation for war had long overtaken any particular attention to health and safety measures. The prevailing policy culture provided minimal financial compensation to workers incapacitated through respiratory illnesses. While historians have investigated the history of occupational health in the coalfield, no detailed analysis has been undertaken on the government's response. This article will provide an in-depth analysis of the area experiencing the highest incidence of respiratory illnesses in wartime – the south Wales coalfield. It will examine the steps attempted by the government and the trade unions to address these issues, and show how the experiences in south Wales provided the platform for national changes in coalmining practices.